Crown Ether Base: Highly Active, Regioselective and Reusable Catalytic Systems for Double Bond Migration in Allylic Compounds. Issue 23 (16th August 2017) - Krompiec, Stanisław; Marcol, Beata; Zych, Dawid; Kurpanik, Aneta; Danikiewicz, Witold; Matussek, Marek; Kuźnik, Nikodem
Abstract: The highly active, reusable and regioselective crown ethers bases catalytic systems, especially 15‐Crown‐5/NaOH, 18‐Crown‐6/KOH, dibenzo‐18‐Crown/6‐t‐BuOK, and 18‐Crown‐6/t‐BuOK, for double bond migration in various allyl and diallyl compounds have been presented. Allyl and/or diallyl: arenes and heteroarenes, ethers, acetal, sulfides, selenide, sulfoxides, imines, phosphine, and phosphine oxide were smoothly converted into their corresponding 1‐propenyl derivatives under very mild conditions. Some of the C, O‐ and O, S‐diallyl compounds were fully regioselectively isomerized to allyl‐(1‐propenyl) derivatives. An unprecedented and significant effect of increasing the reaction rate and shortening the quantitative reaction conversion time without decreasing the selectivity under ultrasound‐assisted conditions was observed. Various solvents, including low‐boiling point ones containing only C, H and/or O atoms, such as DMFL, DME, THF, Et2 O, toluene, and 1, 4‐dioxane, can be used instead of the most frequently used DMSO. Remarkably highly effective recycling of 18‐Crown‐6/t‐BuOK and dibenzo‐18‐Crown‐6‐t‐BuOK catalytic systems for isomerization of low‐boiling or high‐boiling point allyl compounds respectively and crown ethers from all examined catalytic systems was developed. The opportunity to effectively combine the double bond migration with in situ generation of nitrile oxide and finally 1, 3‐DC‐cycloaddition into one pot variant synthesis of isoxazolines from Qallyl has also been announced. Abstract : Highly active, reusable, regioselective and in many cases Z‐stereoselective and ultrasound‐accelerated crown ethers‐bases catalytic systems, especially 15‐Crown‐5/NaOH, 18‐Crown‐6/KOH, dibenzo‐18‐Crown‐6‐ t ‐BuOK, and 18‐Crown‐6/ t ‐BuOK, for double bond migration in various allyl and diallyl compounds have been presented. Various solvents, including low‐boiling point ones containing only C, H and/or O atoms, can be used instead of the most popular DMSO. The opportunity to effectively combine the double bond migration with in situ generation of nitrile oxide and finally 1, 3‐DC‐cycloaddition into the one‐pot variant synthesis of isoxazolines from Qallyl has also been announced.